Physicochemical Quality, Polyphenol Profiles, and Postharvest Performance of Florida Pearl® ‘FL 16.78-109’ White Strawberries Compared to the Red Cultivar ‘Florida Brilliance’ - Alyssa Nicole Smith; Maria Cecilia do Nascimento Nunes (Foods, 2023)
White-fruited strawberry cultivars have recently become popular due to their exotic appearance and flavor, but more needs to be known about their overall quality and postharvest performance. The objective of this study was to characterize and compare the overall quality of the white-fruited strawberry Florida Pearl® ‘FL 16.78-109’ against the commercial, red-fruited strawberry ‘Florida Brilliance’ at harvest and during cold storage (1 °C). Results showed that harvest date and weather conditions contributed to significant differences in fruit quality, regardless of the cultivar. However, Pearl was softer at harvest and had lower total phenolic and anthocyanin contents but was less acidic and had higher total sugars and ascorbic acid contents than Brilliance. Pearl major polyphenols were kaempferol 3-glucoside, quercetin 3-glucoside, quercetin, and gallic acid, while for Brilliance epicatechin, pelargonidin, pelargonidin 3-glucoside, and ferulic acid were the major polyphenol compounds identified. After cold storage, Pearl lost less weight than Brilliance and showed a less dramatic decline in individual polyphenols. Pearl and Brilliance anthocyanins and phenolic acids were the polyphenol groups most affected by cold storage because they showed the highest decline from harvest to the end of storage. Cold storage also had different effects on other polyphenols, but the effect was cultivar-dependent. Overall, white strawberries have a unique appearance, are sweet, have an excellent bioactive profile, and can maintain good postharvest quality.